THEORETICAL ANALYSIS OF THE MAIN CONTEMPORARY THEORIES OF VICTIMIZATION DEVELOPED WITHIN FOREIGN SCIENCE - O. O. Andronnikova (Вестник Кемеровского государственного университета, 2015)
The paper provides an overview of the main theories of victimization popular abroad. The work is aims to overcome the lack of information about the development of victimology abroad, and the main foreign approaches to the study of human victimization. The author considers the concept of “the lifestyle/exposure theory”, personal characteristics and abnormal interpersonal relations. The concept of «peer victimization» is presented as a basis for the consequences. The study shows that the characteristic disorders (low self-esteem and impaired dignity) are present in all members of the victimization process. The effects of various forms of intimidation in the early age and adolescence were studied. The specifics of cyberbullying as a form of violence are highlighted. The role of the theories of gender, race, age influence in the development of approaches to victimization of the individual is revealed. The mechanism of secondary victimization and the effect of social contamination are described. The theories revealing the specifics of victimization of underage refugees are suggested. The author proposes an analysis of various activities to prevent violence among young teenage peers, their effectiveness is evaluated as well. The novelty of the analysis lies in the dissemination of international experience in the field of Russian victimology.